Nitrogen removal characteristics and mechanisms of the assimilation-dominated and acid-tolerant heterotrophic nitrifying-aerobic denitrifying Acinetobacter soli HY24 - Yuanli Wang; Wei Xu; Fuyang Li; Song Tang; Xin Tan; Shufang Tian; Xiaolong Wu; Shenghua Wei; Jie Zhao; Yequan Sheng; Yanbin Li (Journal of Water Process Engineering, 2026)

Comparative evaluation of bio-additives for promoting typical PPCPs degradation and reducing ecological risk during sewage sludge composting - Jishao Jiang; Yanbin Huang; Zhuyu Tang; Kai Liu; Shipeng Wang; Yunbei Li; Jinghua Lv; Chunyan Zhang; Dong Liu; Parag Bhople; Ke Cheng (Journal of Environmental Chemical Engineering, 2026)

Contributions and mechanisms of bioclogging-induced oxygen-limited microsites to nitrogen removal in porous media - Ping Tang; Hui Shuai; Zuan Yang; Qihang Cen; Yanbin Mao; Junjie Wang; Yongchao Zhou (Bioresource Technology, 2026)

Insight into the inhibitory role of rhamnolipid in the adsorption of neonicotinoid pesticides onto biochars - Songting Wang; Bin Wang; Kunyu Wen; Yanbin Ma; Usman Farooq; Zhichong Qi; Taotao Lu; Li Zhang; Shuangcheng Tang (Journal of Contaminant Hydrology, 2026)

Interpretable SR model development and validation for multi-objective optimization of lightweight and crashworthiness of vehicle front-end structures - Yanbin Lu; Changlei Zhang; Bo Liu; Yongxin Tang; Yiben Zhang; Dajiang Chen (Engineering Structures, 2026)

Advocating for sustained and site-specific restoration initiatives: Ecopath model-based evaluation of eutrophic bay ecosystems in East China Sea - Rongliang Zhang; Lu Shou; Xu Wang; Lukuo Ma; Guodong Li; Lang Chen; Yanbin Tang; Qinghe Liu; Yibo Liao; Jiangning Zeng; Wei Huang (Ocean & Coastal Management, 2026)

Hierarchically assembled UiO-66@PIL@PP core-shell catalyst: Synergistic integration of catalysis and CO2 enrichment for efficient cycloaddition - Zhenzhu Tang; Qian Zhang; Baowen Lin; Yunliang Yu; Yanbin Zeng; Chao Zou; Guanqun Xie; Xiaoxia Wang (Journal of Environmental Chemical Engineering, 2026)

Non-indigenous plant expansion reconstructing benthic food web in tidal flats of China - Ouwen Shao; Lu Shou; Qiang Liu; Yanbin Tang; Rongliang Zhang; Yingting Shen; Zhi Yang; Jiangning Zeng; Xiaojun Yan; Yibo Liao (Journal of Environmental Management, 2026)

Hierarchical Cu Ni micro-nanocone arrays as stable lithium metal hosts - Qiulong Tang; Guang Jiang; Jilu Zhao; Qingyu Dong; Jingshu Wang; Haiyang Zhang; Jianxin Ou; Xuechun Wang; Rong Huang; Hui Shao; Jun Ge; Xuefeng Gao; et al. (Chemical Engineering Journal, 2026)

Spatial patterns and environmental drivers of evapotranspiration across the Chinese Grassland Transect - Lexin Ma; Zhi Chen; Tianxiang Hao; Meng Yang; Quanhong Lin; Weikang Zhang; Lang Han; Zhaogang Liu; Mingyu Sun; Yong Lin; Xianjin Zhu; Shiping Chen; et al. (Journal of Hydrology, 2026)

Physiological and molecular responses to sodium acetate addition and supplementation in the two stages of Haematococcus pluvialis - Yanbin Li; Weizhao Han; Na Li; Tian Xie; Xin Tan; Song Tang; Yequan Sheng; Bangxiang He (Journal of Oceanology and Limnology, 2026)

Assessment of benthic ecological quality status of small estuaries using multiple biotic indices in East China Sea - Xin Wang; Lihu Xiong; Hengtao Xu; Changsheng Tang; Yanbin Tang; Rongliang Zhang; Lu Shou; Yibo Liao (Marine Pollution Bulletin, 2026)

Biogeochemical controls on the co-occurrence of mid-depth pH and DO minima in the inner shelf of the East China Sea - Dewang Li; Zhongqiang Ji; Bin Wang; Chen Zeng; Haiyan Jin; Zhibing Jiang; Xiao Ma; Qinyu Liu; Yixuan Tao; Yanbin Tang; Hongliang Li; Feng Zhou; et al. (Marine Pollution Bulletin, 2026)

Responses of mesozooplankton to extreme positive Indian Ocean Dipole (pIOD) and cold-core eddy in the eastern Equatorial Indian Ocean and southern Bay of Bengal during 2019/2020 winter - Ping Du; Xiao Ma; Yuanli Zhu; Ruijie Ye; Shenran Zhang; WNC Priyadarshani; P.A.K.N. Dissanayake; Haifeng Zhang; Yibo Liao; Yanbin Tang; Zhibing Jiang; Hongliang Li; et al. (Progress in Oceanography, 2026)

Coupled design of surface chemistry and spatial topology enabling lithiophilic host for stable Li metal batteries - Nan Zheng; Chao Yang; Qingyu Dong; Shoulei Hu; Qiulong Tang; Jianxin Ou; Huihui Wang; Jingshu Wang; Haiyang Zhang; Jun Ge; Hui Shao; Yanbin Shen; et al. (Chemical Engineering Journal, 2025)

Water availability and hydrological connectivity mediate the responses of alpine soil prokaryotes to temperature changes at the watershed scale - Wencong Lv; Liyuan Ma; Jianqing Du; Li Tang; Biao Zhang; Danhong Chen; Qiang Liu; Shutong Zhou; Zhe Pang; Lin Chen; Yanbin Hao; Kai Xue; et al. (Journal of Environmental Management, 2025)

Revealing the influence of physicochemical parameters on the taxonomic and functional diversity of macrobenthos in hangzhou bay, China - Kangning Jia; Yibo Liao; Yanbin Tang; Rongliang Zhang; Yangjie Li; Lu Shou (Estuarine, Coastal and Shelf Science, 2025)

Organic fertilizer application reduce ammonia volatilization in an acidic soil - Cai Gan; Yanbin Jiang; Yan Wang; Shan Lin; Yue Luo; Huabin Li; Yunwei Li; Niannian Tang; Yang Fei; Ronggui Hu (Agriculture, Ecosystems & Environment, 2025)

Inhibition of soluble epoxide hydrolase ameliorates cerebral blood flow autoregulation and cognition in alzheimer's disease and diabetes-related dementia rat models - Chengyun Tang; Jane J. Border; Huawei Zhang; Andrew Gregory; Shan Bai; Xing Fang; Yedan Liu; Shaoxun Wang; Sung Hee Hwang; Wenjun Gao; Gilbert C. Morgan; Jhania Smith; et al. (GeroScience, 2025)

Assessment of macrobenthos in evaluating the restoration effects of artificial mangrove planting on tidal flats in Zhejiang, China - Ouwen Shao; Yangjie Li; Weifang Gu; Rongliang Zhang; Yanbin Tang; Hengtao Xu; Lu Shou; Jiangning Zeng; Yibo Liao (Marine Environmental Research, 2025)

Mechanical stable composite electrolyte for solid-state lithium metal batteries - Wenlong Zhao; Huihui Wang; Qingyu Dong; Hui Shao; Yanyan Zhang; Yuxin Tang; Yanbin Shen; Liwei Chen (Chemical Engineering Journal, 2025)

Spatiotemporal distribution patterns of macrobenthic communities and their relationship with environmental factors in the Shengsi Archipelago (Zhejiang, China) - Lingxiang Jin; Yibo Liao; Peisong Yu; Yanbin Tang; Qinghe Liu; Rongliang Zhang; Lu Shou; Jiangning Zeng; Quanzhen Chen (Acta Oceanologica Sinica, 2025)

Spatial distribution and risk assessment of mercury in soils over the Tibetan Plateau - Xiufeng Yin; Wenting Zhou; Yanbin Su; Cuiwen Tang; Junming Guo; Zhiwei Liu; Yingying Wang; Xiaohui Zhang; Dipesh Rupakheti; Shichang Kang (Science of The Total Environment, 2024)

Response of macrobenthic communities to a Spartina alterniflora management project on tidal flats in Hangzhou Bay, China - Jingyi Ye; Yibo Liao; Yanbin Tang; Qinghe Liu; Rongliang Zhang; Jiangning Zeng; Lu Shou (Regional Studies in Marine Science, 2024)

Phylogeographical analysis of Nerita yoldii revealed its geographical distribution pattern and drivers of population divergence in the Northwestern Pacific region - Yanbin Tang; Rongliang Zhang; Qinghe Liu; Lu Shou; Yibo Liao (Frontiers in Marine Science, 2024)
The distinctive tectonic settings and hydrological environments of the marginal seas in the Northwestern Pacific render them a focal point for investigating marine speciation and population diversity. In this study, we focused on understanding the phylogeography and demographic history of Nerita yoldii , a species commonly found in rocky intertidal areas. We examined the COI gene sequences from nine populations of the Northwestern Pacific. The analysis revealed four lineages comprising 35 haplotypes, with the majority of variation found within populations. Approximate Bayesian computation analysis supported the scenario that lineages B and C diverged first, and subsequently, lineage A and D originated from lineage C. Mismatch distribution analysis and neutrality tests suggested demographic expansion of lineage C primarily during the Pleistocene epoch of the Quaternary period, with expansion time estimated at approximately 38,000 years ago. Artificial rocky structures along the northern Changjiang coast, combined with global warming, could possibly facilitate the northward migration of N. yoldii larvae in recent decades. This has resulted in a shift in the species’ northern boundary. This study not only unveils the historical, present, and future impacts of climate and environmental changes on intertidal macrobenthos but also furnishes biological evidence crucial for comprehending related geological historical events. Moreover, it offers insights into the future trajectory of intertidal macrobenthos development and serves as a foundation for guiding future biological conservation efforts.

Effect of lactic acid bacteria fermentation on spray-dried egg yolk powder: Powder characteristics, structural properties and gastrointestinal digestibility - Zhe Li; Yanbin Song; Qinyue Tang; Xiang Duan; Long Sheng (Innovative Food Science & Emerging Technologies, 2024)

Warming decouples associations between microbial network complexity and ecosystem multifunctionality in alpine grasslands - Kui Wang; Kai Xue; Wenjing Liu; Biao Zhang; Wenchao Wu; Runchen Zhao; Lizhen Cui; Zongsong Wang; Shutong Zhou; Li Tang; Junfu Dong; Jianqing Du; et al. (Agriculture, Ecosystems & Environment, 2024)

Power law in species–area relationship overestimates bacterial diversity in grassland soils at larger scales - Biao Zhang; Kai Xue; Wenjing Liu; Shutong Zhou; Shipeng Nie; Yichao Rui; Li Tang; Zhe Pang; Linfeng Li; Junfu Dong; Cong Xu; Lili Jiang; et al. (Global Ecology and Biogeography, 2024)
Aim Species–area relationships (SAR) are widely utilized for estimating the species richness and its spatial turnover across various scales. Despite the prevalent characterization of SAR using the power law in many microbial community studies, its efficacy remains unvalidated. This study aims to characterize the microbial SAR and its mechanisms in alpine grassland soils on the Qinghai‐Tibet Plateau (QTP). Location Qinghai‐Tibet Plateau, China. Time Period August 2014. Major Taxa Studied Soil bacteria. Methods Soil samples were collected from five alpine grassland sites on the QTP. Employing a nested sampling strategy at each site, soil samples were collected in plot sizes ranging from 0.5 × 0.5 m 2 to 2048 × 2048 m 2 . Soil bacterial communities were analysed by sequencing 16S ribosomal RNA gene amplicons using an Illumina MiSeq. Results The bacterial SAR exhibited a logarithmic power law ( R 2 : 0.952–0.999), outperforming the power law ( R 2 : 0.701–0.852). Consequently, the most widely adopted power law led to an overestimation of species richness by up to 15.07% in areas >256 × 256 m 2 , and the regional maximum theoretical richness based on Chao1 by up to 9.88%. Mechanistically, the passive sampling hypothesis was refuted through the rarefied species richness analysis, and the disproportionate effect hypothesis was rejected based on analyses of the effective numbers of species number conversions for the probability of interspecific encounters ( S PIE ). Notably, Pearson and multiple linear regression analyses indicated that the spatial turnover of bacterial richness was determined by the environmental heterogeneity ( R 2 : 0.855–0.999), rather or better than environmental variables themselves, supporting the ‘environment heterogeneity hypothesis’. Main Conclusions Soil bacterial SAR in alpine grasslands exhibited a logarithmic power relationship. Spatial turnover was primarily governed by the environmental heterogeneity. In contrast, the traditional power law leads to an overestimation of soil bacterial diversity at the regional scale.

Decadal changes of macrofauna community in a semi-enclosed Bay of Yueqing in East China Sea - Qinghe Liu; Yibo Liao; Jiangning Zeng; Yanbin Tang; Rongliang Zhang; Qiang Liu; Lu Shou (Marine Pollution Bulletin, 2024)

Methylmercury photodegradation in paddy water: An overlooked process mitigating methylmercury risks - Huan Zhong; Hangyu Zhou; Yanbin Li; Chengjun Li; Martin Tsz-Ki Tsui; Carl P.J. Mitchell; Yang Zhou; Yanan Yang; Long Chen; Hongqiang Ren; Wenli Tang (Water Research, 2024)

Spatial and temporal variations in the pollution status and sources of mercury in the Jiaozhou bay - Zhengwen Zhou; Zhekai Tang; Huiling Wang; Ke Liu; Yingjun Wang; Xiaotong Xiao; Yongguang Yin; Guangliang Liu; Yong Cai; Yanbin Li (Environmental Pollution, 2024)

Differences in background environment and fertilization method mediate plant response to nitrogen fertilization in alpine grasslands on the Qinghai-Tibetan Plateau - Shun He; Jianqing Du; Yanfen Wang; Lizhen Cui; Wenjing Liu; Yifan Xiao; Qinwei Ran; Linfeng Li; Zuopei Zhang; Li Tang; Ronghai Hu; Yanbin Hao; et al. (Science of The Total Environment, 2024)

Climate-shaped vegetation dominated the spatial pattern of the Bowen ratio over terrestrial ecosystems in China - Mingyu Sun; Guirui Yu; Zhi Chen; Tianxiang Hao; Meng Yang; Xianjin Zhu; Weikang Zhang; Lang Han; Zhaogang Liu; Lexin Ma; Xiaojun Dou; Yuan Yao; et al. (Agricultural and Forest Meteorology, 2024)

Precipitation consistently promotes, but temperature oppositely drives carbon fluxes in temperate and alpine grasslands in China - Zhaogang Liu; Zhi Chen; Meng Yang; Tianxiang Hao; Guirui Yu; Xianjin Zhu; Weikang Zhang; Lexin Ma; Xiaojun Dou; Yong Lin; Wenxing Luo; Lang Han; et al. (Agricultural and Forest Meteorology, 2024)

The Epidemiology of Tinea Capitis in Guangxi Province, China - Dongyan Zheng; Tianwei Liang; Weixuan Wu; Najwa Al-Odaini; Kaisu Pan; Lan Huang; Guomei Huang; Lulu Tang; Xinlei Li; Shao He; Huahui Jian; Nibo Wei; et al. (Mycopathologia, 2023)

Navigating the landscape of global sustainable livelihood research: past insights and future trajectory - Tong Li; Ranjay K. Singh; Lizhen Cui; Zhihong Xu; Hongdou Liu; Francesco Fava; Shalander Kumar; Xiufang Song; Li Tang; Yanfen Wang; Yanbin Hao; Xiaoyong Cui (Environmental Science and Pollution Research, 2023)

Middle-Scale Spatial and Temporal Patterns in Estuaries: Rocky Intertidal Macrobenthic Communities in the Hangzhou Bay and Zhoushan Sea - Hanren Liu; Hengtao Xu; Yanbin Tang; Zhifu Wang; Qinghe Liu; Rongliang Zhang; Lu Shou; Jiangning Zeng; Yibo Liao (Estuaries and Coasts, 2023)

Ecological risk assessment of trace metals in sediments and their effect on benthic organisms from the south coast of Zhejiang province, China - Zhengjia Zhao; Qiang Liu; Yibo Liao; Peisong Yu; Yanbin Tang; Qinghe Liu; Xiaolai Shi; Lu Shou; Jiangning Zeng; Quanzhen Chen; Jianfang Chen (Marine Pollution Bulletin, 2023)

Effects of temperature shock on the survival of different life stages of large yellow croaker (Larimichthys crocea) by simulated power plant cooling water - Sujie Tian; Konglin Zhou; Yibo Liao; Yanbin Tang; Qinghe Liu; Rongliang Zhang; Lu Shou; Jiangning Zeng (Frontiers in Marine Science, 2022)
Seawater temperatures have increased with global climate change. Coolant water discharged from coastal nuclear power-generating and coal-powered plants, coupled with already increasing seawater temperatures, can adversely affect local fish communities. A sudden drop in temperature caused by the winter shutdown of power plants can also affect fish health and behavior. To assess the effects of temperature change on fish populations, we subjected early life stages of the once commercially important large yellow croaker ( Larimichthys crocea ) to various water temperature experiments. Fertilized eggs showed the highest hatching rate at 23.4°C and the lowest rate of deformity in hatched larvae at 23.0°C. We determined the incipient lethal temperature for each life stages using derivation models. Ranges between the upper and lower incipient lethal temperatures increased during development from yolk-sac larvae to juveniles, especially in response to cold shock, indicating that later developmental stages in this species are more tolerant of temperature fluctuations. However, thermal tolerance is not solely determined by life stage. Our results suggest that rapid changes in seawater temperature caused by power plant coolant water discharges may significantly affect early developmental stages of fish. Critical thermal maximum tests indicate that the seawater heating rate is significantly negatively correlated with survival time and affects the critical thermal maximum value of L. crocea . On the basis of our determination of incipient lethal temperatures, emergency measures could be taken to avoid adverse economic and ecological impacts due to changes in seawater temperature caused by coolant water discharges.

Spatial and temporal distribution of macrobenthos communities and their relationship with secondary front in Hangzhou Bay - Kangning Jia; Yanbin Tang; Qinghe Liu; Rongliang Zhang; Yibo Liao; Lu Shou; Jiangning Zeng; Quanzhen Chen; Jianfang Chen (Frontiers in Marine Science, 2022)
Water quality in Hangzhou Bay is inferior (grade 5) because of discharged from Yangtze River and Qiantang River, and from factories around the bay. This study analyzed relationships between the environment and macrobenthic communities at 44 stations throughout Hangzhou Bay, based on samples collected in 2006, from 2016–2018, and in 2021. Long-term spatial and temporal changed in macrobenthos, and the influence of secondary water fronts on community composition, were discussed. Macrobenthos in Qiantang River Estuary was numerically, primarily dominated by crustaceans, and elsewhere by polychaetes. Species that differ most in abundance between four identified regions in the bay were the amphipod Corophium sinensis , clam Potamocorbula laevis , and polychaete Amaeana occidentalis . The abundance and biomass of macrobenthos in different regions differs significantly. Taxa were allocated to six feeding guilds: filter feeders and omnivores predominate in Qiantang River Estuary and south of Hangzhou Bay, while surface and subsurface deposit feeders predominate in sediments north of Hangzhou Bay and in the bay mouth area. Negative correlations were apparent between the abundances of polychaetes Nephtys polybranchia , Magelona japonica , Heterospio sinica , Sabella sp. and A. occidentalis and salinity and pH, while positive correlations were apparent between those of Sternaspis chinensis and Capitellidae indet. Fine-grained fraction (silt and clay) and mid-salinity were more suitable for macrobenthos. The numbers and biomasses of macrobenthic species in the Hangzhou Bay frontal area increased significantly relative to values in adjacent areas. The difference of each area near the front was more than 94%, and the main difference species were polychaetes and mollusks. Our baseline data for this region might ultimately contribute towards improved conservation of regional macrobenthos, and a better understanding of ecosystem health in this highly polluted bay.

Association between resting-state functional connectivity of amygdala subregions and peripheral pro-inflammation cytokines levels in bipolar disorder - Jiaying Gong; Guanmao Chen; Feng Chen; Shuming Zhong; Pan Chen; Hui Zhong; Shunkai Lai; Guixian Tang; Jurong Wang; Zhenye Luo; Zhangzhang Qi; Yanbin Jia; et al. (Brain Imaging and Behavior, 2022)

Characteristics and trends of grassland degradation research - Tong Li; Lizhen Cui; Michele Scotton; Junfu Dong; Zhihong Xu; Rongxiao Che; Li Tang; Shuohao Cai; Wenchao Wu; Davide Andreatta; Yanfen Wang; Xiufang Song; et al. (Journal of Soils and Sediments, 2022)

Using Ecopath Models to Explore Differences in Ecosystem Characteristics Between an Artificial Reef and a Nearby Natural Reef on the Coast of the North Yellow Sea, China - Rongliang Zhang; Qianqian Zhang; Jianmin Zhao; Zhongxin Wu; Hui Liu; Lu Shou; Yibo Liao; Qinghe Liu; Yanbin Tang; Jiangning Zeng (Frontiers in Marine Science, 2022)
The comparison of trophic structure and energy flow between natural and artificial reefs is imperative to evaluate whether these man-made structures work similarly to comparable natural reefs. Here, to characterize the potential difference in functioning between two types of reef ecosystems, two trophic models (Ecopath) at an artificial reef and an adjacent natural reef on the coast of the north Yellow Sea, China, were established. Both Ecopath models were divided into 18 functional groups from primary producers (algae and phytoplankton) and detritus to predatory species (e.g., Sebastes schlegelii ). Model outputs showed that the ecosystem scale was smaller in the artificial reef (total system throughput (TPP) = 6,455.47 t·km −2 ·year −1 ) relative to its natural counterpart (TPP = 9,490.48 t·km −2 ·year −1 ). At both reef types, a large proportion of energy occurred at trophic levels I and II, and most of the primary production was utilized through a detritus pathway. This result implies a bottom-up energy flow control for both cases. However, two types of reef systems were behaving in a reasonable manner, as mean transfer efficiencies were similar to the Lindeman efficiency (10%). The ecosystem maturity of the artificial reef is not comparable to that of the natural reef for its inferior value of total primary production/total respiration (TPP/TR). Moreover, both the connectance index (CI) and system omnivory index (SOI) were slightly higher at the artificial reef relative to the natural reef as well as other coastal systems with parallel latitudes, suggesting that the current artificial system has formed complicated interspecies relations and high-level stability. This work updates our knowledge about the functioning evolvement of established artificial reefs and provides a baseline for the efficient management of coastal zones and further investigations.

Transcriptome Sequencing of the Pale Anemones (Exaiptasia diaphana) Revealed Functional Peptide Gene Resources of Sea Anemone - Jinxing Fu; Yanbin He; Chao Peng; Tianle Tang; Aihua Jin; Yanling Liao; Qiong Shi; Bingmiao Gao (Frontiers in Marine Science, 2022)
Sea anemone venom is a marine drug resource library with pharmacological and biotechnology value, and it contains complex and diverse functional peptide neurotoxins. However, the venom components of only a limited number of sea anemone species have been globally evaluated by transcriptomics and proteomics. In this study, 533 putative protein as well as peptide toxin sequences were found on a large scale from dissimilar developmental stages of sea anemone Exaiptasia diaphana , which can be divided into 75 known superfamilies according to the predicted functions. Among them, the proportion of protein is 72.98%, and its main families are metalloproteases, chymotrypsinogen like, collagen, pancreatic lipase-associated protein like, and G-protein coupled receptor, while the proportion of peptides is 27.02%, and main families are ShK domain, thrombin, Kunitz-type, defensin, as well as insulin-like peptide. Finally, typical anemone peptide neurotoxins were screened, and the 3D structure and pharmacological activity of these anemone peptide neurotoxins were predicted by homology modeling. We elucidate on a valuable high-throughput approach for obtaining sea anemone proteins and peptides. Our findings form the basis for targeted studies on the diversity as well as pharmacological effects of sea anemone peptide neurotoxins.

The spatiotemporal evolution of urbanization of the countries along the Belt and Road Initiative using the compounded night light index - Panli Tang; Jiejun Huang; Han Zhou; Huan Wang; Wei Huang; Xiaochi Huang; Yanbin Yuan (Arabian Journal of Geosciences, 2021)

Responses of macrobenthic communities to patchy distributions of heavy metals and petroleum hydrocarbons in sediments: A study in China’s Zhoushan Archipelago - Yanbin Tang; Qiang Liu; Yibo Liao; Konglin Zhou; Lu Shou (Acta Oceanologica Sinica, 2021)

Seasonal distribution of macrobenthos and its relationship with environmental factors in Yellow Sea and East China Sea - Lu Shou; Yibo Liao; Yanbin Tang; Jianfang Chen; Zhibing Jiang; Aigen Gao; Quanzhen Chen (Journal of Oceanology and Limnology, 2018)

Precipitation drives the biogeographic distribution of soil fungal community in Inner Mongolian temperate grasslands - Di Wang; Yichao Rui; Kai Ding; Xiaoyong Cui; Yanbin Hao; Li Tang; Zhe Pang; Biao Zhang; Shutong Zhou; Kui Wang; Yanfen Wang (Journal of Soils and Sediments, 2018)